Polymer composition, single layer film and laminate
Patent Information
- Application Number
- JP2023128558
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-20
AI Technical Summary
【0017】 本発明によれば、押出ラミネート成形において成形性に優れ、高温雰囲気下においても基材層との接着性を良好に維持し得る重合体組成物を提供することができる。
Smart Images

Figure 2025024447000001
Abstract
Description
[Technical field]
[0001] The present invention relates to polymer compositions, monolayer films and laminates. [Background technology]
[0002] Laminates obtained by laminating a substrate layer and an adhesive layer made of an adhesive polymer composition are widely used as materials for packaging contents for which maintaining the quality is important, such as industrial materials, automobiles, foods, medicines, etc. As the substrate layer of the laminates used for these applications, when the packaging material requires formability and material strength, a metal layer made of a metal material or a metal layer made of a composite material of metal and resin is used. Known methods for laminating such a base layer and an adhesive layer include extrusion lamination, thermal lamination, co-extrusion, etc., of which extrusion lamination is preferably used due to its high production speed.
[0003] However, in the extrusion lamination molding, since a molten adhesive polymer composition or the like is laminated at high speed onto the surface of a substrate layer that is already in the form of a film, the adhesive strength between the two layers is not necessarily high. In recent years, the demand for durability and heat resistance of the laminate has been increasing, and there are an increasing number of cases where a high adhesive strength is required even in a high temperature atmosphere.
[0004] As a method for solving such problems, for example, a method is known which uses a polymer composition containing a polypropylene-based resin containing modified polypropylene obtained by modifying polypropylene with an unsaturated carboxylic acid or a derivative thereof, a propylene-based copolymer, an ethylene-α-olefin copolymer, and polyethylene (see Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2012-188662 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, in a laminate having an adhesive layer and a base layer using the polymer composition described in Patent Document 1, which is obtained by extrusion lamination molding, the adhesive strength in a high-temperature atmosphere exceeding 100°C is insufficient, and there is room for improvement.
[0007] An object of the present invention is to provide a polymer composition which has excellent moldability in extrusion lamination molding and can maintain good adhesion to a substrate layer even in a high-temperature atmosphere. [Means for solving the problem]
[0008] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that the above-mentioned problems can be solved by using a polymer composition containing a modified propylene-based polymer obtained by modifying a propylene-based polymer with an unsaturated carboxylic acid and / or a derivative thereof, a propylene-based copolymer satisfying a specific storage modulus, an ethylene-α-olefin copolymer satisfying a specific density, and a high-pressure low-density polyethylene, thereby completing the present invention.
[0009] That is, the present invention relates to the following.
[0010] A first aspect of the present invention is a polymer composition containing the following components (A) to (D). Component (A): A modified propylene-based polymer obtained by modifying a propylene-based polymer with an unsaturated carboxylic acid and / or its derivative. Component (B): at least one propylene-based copolymer selected from the group consisting of propylene-ethylene copolymers, propylene-α-olefin copolymers, and propylene-ethylene-α-olefin copolymers, the propylene-based copolymer having a storage modulus at 120°C of 6 to 300 MPa. Component (C): Density measured by underwater displacement method according to JIS K 7112:1999 is 0.855 to 0.910 g / cm 3 Ethylene-α-olefin copolymer Component (D): High-pressure low-density polyethylene
[0011] A second aspect of the present invention relates to the polymer composition of the first aspect, In the polymer composition, the content of the component (B) is 45 to 75 mass % based on the total content of the components (A) to (D).
[0012] A third aspect of the present invention relates to the polymer composition of the first or second aspect, The polymer composition is such that the component (B) is a propylene-ethylene copolymer.
[0013] A fourth aspect of the present invention relates to a polymer composition comprising the polymer composition according to any one of the first to third aspects, In the polymer composition, the content of propylene units in the component (B) is 90 to 99.5% by mass.
[0014] A fifth aspect of the present invention is a monolayer film comprising the polymer composition of any one of the first to fourth aspects.
[0015] A sixth aspect of the present invention is a laminate comprising an adhesive layer containing the polymer composition of any one of the first to fourth aspects, and a substrate layer.
[0016] A seventh aspect of the present invention is the laminate of the sixth aspect, The laminate is a metal layer made of a metal material or a metal layer made of a composite material of a metal and a resin. Effect of the Invention
[0017] According to the present invention, it is possible to provide a polymer composition which is excellent in moldability in extrusion lamination molding and can maintain good adhesion to a substrate layer even in a high-temperature atmosphere. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The following describes in detail the embodiments of the present invention, but the following embodiments are merely examples of the embodiments of the present invention and the present invention is not limited thereto. The present invention can be carried out in any modified form without departing from the gist of the present invention. In this specification, when "~" is used with a numerical value or a physical property value enclosed therein, the values before and after the "~" are included in the expression.
[0019] [Polymer composition] The polymer composition according to this embodiment is characterized by containing the following components (A) to (D). Component (A): A modified propylene-based polymer obtained by modifying a propylene-based polymer with an unsaturated carboxylic acid and / or its derivative. Component (B): at least one propylene-based copolymer selected from the group consisting of propylene-ethylene copolymers, propylene-α-olefin copolymers, and propylene-ethylene-α-olefin copolymers, the propylene-based copolymer having a storage modulus at 120°C of 6 to 300 MPa. Component (C): Density measured by underwater displacement method according to JIS K 7112:1999 is 0.855 to 0.910 g / cm 3 Ethylene-α-olefin copolymer Component (D): High-pressure low-density polyethylene
[0020] <Mechanism> In the polymer composition according to this embodiment, it is believed that the effects of the present invention can be obtained by each of the components (A) to (D) fulfilling the following roles. Component (A) exerts strong adhesion by hydrogen bonding with the base layer through the unsaturated carboxylic acid or its derivative. Component (B) plays a role in maintaining mechanical properties in the high temperature range. Component (C) promotes stress relaxation by imparting appropriate flexibility. Component (D) is responsible for moldability during molding.
[0021] <Component (A): Modified propylene-based polymer obtained by modifying a propylene-based polymer with an unsaturated carboxylic acid and / or a derivative thereof> The component (A) is a modified propylene-based polymer obtained by modifying a propylene-based polymer with at least one unsaturated carboxylic acid and / or a derivative thereof. The modification is preferably graft modification. Here, "graft modification" means that an unsaturated carboxylic acid and / or a derivative thereof is bonded to a propylene-based polymer. The bond position of the unsaturated carboxylic acid and / or a derivative thereof in the modified propylene-based polymer is not particularly limited, and it is sufficient that the unsaturated carboxylic acid and / or a derivative thereof is introduced to at least one of the main chain terminal and the side chain of the propylene-based polymer. The expression "unsaturated carboxylic acid and / or a derivative thereof" may be expressed as "at least one selected from the group consisting of unsaturated carboxylic acids and derivatives thereof".
[0022] The propylene polymer used as the raw material of component (A) is not limited as long as the content of propylene units exceeds 50% by mass, that is, the content of monomer units other than propylene is less than 50% by mass. The content of propylene monomer units is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.
[0023] The propylene-based polymer is not particularly limited as long as the content of propylene units exceeds 50% by mass, and examples thereof include propylene homopolymers, propylene-ethylene copolymers, propylene-1-butene copolymers, propylene-ethylene-1-butene copolymers, propylene-4-methyl-1-pentene copolymers, copolymers of propylene and ethylene and / or other α-olefins, and copolymers of propylene and other vinyl monomers. Here, the other α-olefins, i.e., α-olefins other than propylene, are not particularly limited, and typically include hydrocarbons having a double bond of 4 to 20 carbon atoms, preferably 4 to 10 carbon atoms. The "other vinyl monomers" are also not particularly limited, and examples thereof include vinyl acetate, vinyl alcohol, (meth)acrylic acid, (meth)acrylic acid alkyl esters, styrene, and styrene derivatives. The propylene-based polymer may be one of the above resins or a mixture of two or more of them.
[0024] The above-mentioned copolymers may be any of block copolymers, graft copolymers, random copolymers, and the like. Among these, the propylene-based polymer is preferably a propylene homopolymer, a propylene-ethylene copolymer, or a blend thereof, and more preferably a propylene homopolymer.
[0025] The density of the propylene polymer measured by the underwater displacement method in accordance with JIS K 7112:1999 is 0.860 to 0.910 g / cm3 in order to obtain excellent moldability and strength. 3 It is preferable that:
[0026] In addition, the MFR (230°C, load 21.2N, orifice diameter 2mm) of the propylene polymer measured in accordance with JIS K 7210:2014 is not particularly limited, but from the viewpoints of uniform mixing with other components and high-speed moldability, it is usually 0.5 to 50g / 10 minutes, preferably 1 to 30g / 10 minutes, and more preferably 2 to 25g / 10 minutes.
[0027] The flexural modulus of the propylene-based polymer is not particularly limited, but is usually in the range of 30 to 2000 MPa, and is preferably 500 MPa or more in order to maintain mechanical strength and prevent material destruction, and is preferably 2000 MPa or less in order to ensure appropriate wettability at the bonding surface and prevent adhesion from decreasing.
[0028] The unsaturated carboxylic acid used for the graft modification of the propylene-based polymer is preferably an α,β-ethylenically unsaturated carboxylic acid, such as acrylic acid, methacrylic acid, ethacrylic acid, maleic acid, fumaric acid, tetrahydrofumaric acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, etc. Examples of derivatives of unsaturated carboxylic acids include acid anhydrides and carboxylates of these unsaturated carboxylic acids, and may further include derivatives such as acid halides, amides, and imides. Of these derivatives, acid anhydrides are preferred.
[0029] Among these, maleic acid and / or its anhydride are particularly suitable. A plurality of these compounds may be used in combination. Furthermore, vinyl silanes such as vinyltrimethoxysilane may be used in combination with the unsaturated carboxylic acid and / or its derivative.
[0030] The graft modification for obtaining the modified propylene-based polymer of component (A) can be carried out by a known method. For example, the polymer can be obtained by a reaction using heat alone, but an organic peroxide or the like that generates radicals during the reaction can be added as a radical generator. In addition, examples of the reaction method include a solution modification method in which the reaction is carried out in a solvent, a melt modification method that does not use a solvent, and the like, and further, other methods such as a suspension dispersion reaction method can be used.
[0031] Examples of the melt modification method include a method in which a propylene-based polymer, an unsaturated carboxylic acid and / or a derivative thereof, and, if necessary, a radical generator described below are mixed in advance and then melt-kneaded in a kneader to cause a reaction, and a method in which a mixture of a radical generator and an unsaturated carboxylic acid and / or a derivative thereof is added from an inlet to a propylene-based polymer molten in a kneader to cause a reaction, etc. For mixing, a Henschel mixer, a ribbon blender, a V-type blender, etc. can usually be used, and for melt kneading, a single-screw or twin-screw extruder, a roll, a Banbury mixer, a kneader, a Brabender mixer, etc. can usually be used.
[0032] As the solution modification method, a method can be used in which a propylene-based polymer is dissolved in an organic solvent or the like, and a radical generator and an unsaturated carboxylic acid and / or a derivative thereof are added thereto to carry out graft copolymerization. The organic solvent is not particularly limited, and for example, an alkyl group-substituted aromatic hydrocarbon or a halogenated hydrocarbon can be used.
[0033] The blending ratio of the propylene-based polymer and the unsaturated carboxylic acid and / or its derivative is not particularly limited, but it is desirable to blend the unsaturated carboxylic acid and / or its derivative in an amount of usually 0.01 to 30 parts by mass, preferably 0.05 to 10 parts by mass, and more preferably 0.1 to 5 parts by mass, per 100 parts by mass of the propylene-based polymer.
[0034] The radical generator is not particularly limited, and examples thereof include dialkyl peroxides such as di-t-butyl peroxide, t-butylcumyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, 1,4-bis(t-butylperoxyisopropyl)benzene, 1,1-bis(t-butylperoxy)cyclohexane, n-butyl-4,4-bis(t-butylperoxy)valerate, 2,2-bis(4,4-t-butylperoxycyclohexyl)propane, 2,2-bis(t-butylperoxy)butane, and 1,1-bis(t-butylperoxy)cyclododecane, t-butylperoxyacetate, t-butylperoxy-2-ethylhexanoate, t-butylperoxypivalate, t-butylperoxylaurate, t-butylperoxybenzoate, t-butylperoxyphenyl per ... Examples of the peroxyesters include ethylperoxyisopropyl carbonate, t-butylperoxymaleic acid, di-t-butylperoxyisophthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-di(benzoylperoxy)hexyne-3, and 2,5-dimethyl-2,5-di(toluylperoxy)hexane; diacylperoxides include di-3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, and dibenzoyl peroxide; hydroperoxides include t-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, p-menthane hydroperoxide, and 2,5-dimethyl-2,5-di(hydroperoxy)hexane; and ketone peroxides include methyl ethyl ketone peroxide and cyclohexanone peroxide. These may be used alone or in combination of two or more.
[0035] These radical generators can be appropriately selected depending on the type and MFR of the raw propylene polymer, the type and reaction conditions of the unsaturated carboxylic acid and / or its derivative, etc., and two or more types may be used in combination. The amount of the radical generator is not particularly limited, but is usually 0.001 to 20 parts by mass, preferably 0.005 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, and particularly preferably 0.01 to 3 parts by mass, relative to 100 parts by mass of the propylene polymer.
[0036] The amount of modification (graft ratio) with the unsaturated carboxylic acid and / or its derivative in the modified propylene-based polymer of component (A) is not particularly limited, but from the viewpoint of adhesion to the base layer, it is usually 0.01 mass% or more, preferably 0.1 mass% or more, and more preferably 0.3 mass% or more, while from the viewpoint of thermal stability and compatibility with other components, it is usually 10 mass% or less, preferably 7 mass% or less, and more preferably 5 mass% or less.
[0037] Here, the modification amount (graft ratio) means the content of unsaturated carboxylic acid and / or its derivative components when measured by an infrared spectrometer. For example, the absorption specific to carboxylic acid and / or its derivatives in a sample press-molded into a sheet having a thickness of about 100 μm, specifically, 1900 to 1600 cm -1 The mass of the grafted portion structure is calculated from the measured value thus obtained, and the ratio of the mass of the grafted portion structure to the mass of the modified propylene-based polymer as 100% by mass is defined as the graft ratio. In addition, in the modification with an unsaturated carboxylic acid and / or a derivative thereof, 100% may not be subjected to the reaction, and unsaturated carboxylic acid and / or a derivative thereof that has not reacted with the propylene-based polymer may remain in the modified polypropylene. However, the modification amount (graft ratio) in this embodiment means the value measured by the above-mentioned method.
[0038] In addition, component (A) can be treated to remove unreacted unsaturated carboxylic acid and / or its derivatives. This treatment method is not particularly limited, but a specific example is a method in which a modified polypropylene resin is placed in a storage tank having a structure that allows gas to be blown in from the bottom of the device, the device is heated to about 100°C with a heater or heat transfer oil, and an inert gas such as nitrogen or air is blown in from the bottom of the device for treatment for 6 to 24 hours.
[0039] In the present embodiment, the modified propylene-based polymer of component (A) may be used alone or in combination of two or more kinds of propylene-based polymers differing in the monomer composition or physical properties, the type of unsaturated carboxylic acid and / or its derivative used for graft modification, or the degree of modification.
[0040] In this embodiment, the content of component (A) relative to the total content of component (A) and components (B) to (D) described below is preferably 0.5 to 35 mass%, more preferably 1 to 25 mass%, and even more preferably 2 to 20 mass%. In addition, when unsaturated carboxylic acid and / or its derivative that has not reacted with the propylene-based polymer remains in the component (A), the content of the component (A) and the total content of the components (A) to (D) are values including the remaining unsaturated carboxylic acid and / or its derivative. The same applies to the content of the component (A) and the total content of the components (A) to (D) discussed hereinafter in this specification.
[0041] <Component (B): at least one propylene-based copolymer selected from the group consisting of propylene-ethylene copolymers, propylene-α-olefin copolymers, and propylene-ethylene-α-olefin copolymers, the propylene-based copolymer having a storage modulus at 120°C of 6 to 300 MPa> The propylene-based copolymer used as component (B) is one or more propylene-based copolymers selected from the group consisting of propylene-ethylene copolymers, propylene-α-olefin copolymers, and propylene-ethylene-α-olefin copolymers, and is a propylene-based copolymer having a storage modulus at 120°C of 6 to 300 MPa.
[0042] The lower limit of the storage modulus of component (B) at 120° C. is preferably 7 MPa or more, more preferably 8 MPa or more, and even more preferably 9 MPa or more, from the viewpoint of material strength. On the other hand, the upper limit of the storage modulus at 120° C. of component (B) is preferably 290 MPa or less, more preferably 280 MPa or less, and even more preferably 270 MPa or less, from the viewpoint of adhesion. It is preferable that the storage modulus of component (B) at 120°C is 7 MPa or more, since the adhesive strength is less likely to decrease in a high temperature environment, and it is preferable that the storage modulus is 290 MPa or less, since the initial adhesive strength is less likely to decrease.
[0043] The storage modulus of component (B) was measured using a viscoelasticity measuring device (VES, manufactured by IT Measurement and Control Co., Ltd.). For the measurement, a test piece (thickness 0.4 mm, length 70 mm, width 70 mm) was used, which was prepared by heating 2 g of a polymer sample such as a propylene-based copolymer at 230°C for 3 minutes and hot pressing it under a pressure condition of 230°C and 7 MPa for 2 minutes. The measurement conditions were temperature: -100 to 300°C, frequency: 1 Hz, heating rate: 3°C / min, and strain: 0.03 to 0.1%.
[0044] The storage modulus of component (B) can be controlled, for example, by the content of α-olefin monomer or ethylene monomer contained in the propylene-based copolymer. The storage modulus tends to be small when the content of α-olefin monomer or ethylene monomer is large, and tends to be large when the content of α-olefin monomer or ethylene monomer is small.
[0045] The propylene copolymer of component (B) is one having a propylene unit content of more than 50% by mass, i.e., a content of monomer units other than propylene of less than 50% by mass, and specifically includes a propylene-ethylene copolymer, a propylene-α-olefin copolymer, and a propylene-ethylene-α-olefin copolymer. Here, the α-olefin is not particularly limited, but typically includes a hydrocarbon having a double bond with 4 to 20 carbon atoms, preferably 4 to 10 carbon atoms.
[0046] The above-mentioned copolymers may be any of block copolymers, graft copolymers, random copolymers, and the like.
[0047] From the viewpoint of heat resistance, the content of propylene units in component (B) is preferably from 90 to 99.5 mass %, more preferably from 91 to 99.4 mass %, and even more preferably from 92 to 99.3 mass %.
[0048] Among these, as component (B), a propylene-ethylene copolymer, a propylene-ethylene-butene copolymer, or a blend thereof is preferred, and a propylene-ethylene copolymer is more preferred.
[0049] The density of component (B), measured by the underwater displacement method in accordance with JIS K 7112:1999, is 0.885 to 0.905 g / cm3 from the viewpoint of the balance between flexibility and mechanical strength. 3 It is preferable that:
[0050] In addition, the MFR (230°C, load 21.2 N, orifice diameter 2 mm) of component (B) measured in accordance with JIS K 7210:2014 is not particularly limited, but from the viewpoint of moldability, it is usually 1 to 80 g / 10 min, preferably 3 to 70 g / 10 min, and more preferably 5 to 60 g / 10 min.
[0051] As the component (B), a commercially available product can be suitably used. For example, a product having the above-mentioned properties can be appropriately selected from WINTEC and WELNEX manufactured by Japan Polypropylene Corporation, and Vistamax manufactured by Exxon Mobil Corporation.
[0052] In the present embodiment, the content of component (B) relative to the total content of components (A) to (B) and components (C) to (D) described below is preferably 45 to 75 mass%, more preferably 47 to 73 mass%, and even more preferably 50 to 70 mass%, from the viewpoints of flexibility and heat resistance.
[0053] <Component (C): Density of 0.855 to 0.910 g / cm3 measured by underwater displacement method according to JIS K 7112:1999 3 Ethylene-α-olefin copolymer> The ethylene-α-olefin copolymer of component (C) is an ethylene-α-olefin copolymer having an ethylene unit content of more than 50 mass% based on the total amount of ethylene units and α-olefin units. From the viewpoints of affinity with the polypropylene matrix based on component (A) or component (B) and affinity with component (D), the ethylene unit content is preferably 70 to 90 mass% and the α-olefin unit content is preferably 10 to 30 mass%.
[0054] The α-olefin constituting component (C) is not particularly limited, but examples thereof include propylene, 1-butene, 3-methyl-1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, etc. Among them, α-olefins having 3 to 8 carbon atoms are preferred.
[0055] Furthermore, component (C) may contain other comonomers consisting of ethylene units and α-olefins other than those mentioned above. The content of these comonomers is not particularly limited, but it is preferable that the total content of the comonomer and α-olefin is within the range of the content of the α-olefin units mentioned above. Specific examples of the comonomers include the "other vinyl monomers" mentioned in the description of component (A) above.
[0056] The density of component (C), measured by the underwater displacement method in accordance with JIS K 7112:1999, is 0.855 to 0.910 g / cm3 from the viewpoint of flexibility and adhesion. 3 0.860-0.905g / cm 3 It is preferable that:
[0057] In addition, the MFR (230°C, load 21.2 N, orifice diameter 2 mm) of component (C) measured in accordance with JIS K 7210:2014 is not particularly limited, but from the viewpoints of moldability and compatibility, it is usually 0.2 to 40 g / 10 min, preferably 0.5 to 30 g / 10 min, and more preferably 0.7 to 25 g / 10 min.
[0058] As a suitable component (C), a commercially available product can be used, and for example, one having the above-mentioned properties can be appropriately selected from the "TAFMER" series manufactured by Mitsui Chemicals, Inc.
[0059] In the present embodiment, the content of component (C) relative to the total content of components (A) to (C) and component (D) described below is preferably 5 to 40 mass%, more preferably 7 to 35 mass%, and even more preferably 10 to 30 mass%, from the viewpoint of flexibility.
[0060] <Component (D): High-pressure low-density polyethylene> From the viewpoint of moldability, high-pressure low-density polyethylene is used as component (D). The density of component (D) measured by the underwater displacement method in accordance with JIS K 7112:1999 is greater than 0.910 and less than 0.930 g / cm. 3 The following is preferred:
[0061] The MFR (190°C, load 21.2N) of component (D) measured in accordance with JIS K 7210:2014 is usually 1g / 10min or more, preferably 3g / 10min or more, and usually 30g / 10min or less, preferably 20g / 10min or less, more preferably 15g / 10min or less. By setting the MFR of the high-pressure low-density polyethylene to the lower limit or more, it is preferable that the fine dispersion in the polymer composition is easily maintained. By setting the MFR of the high-pressure low-density polyethylene to the upper limit or less, it is preferable that the high-speed extrusion laminate moldability is easily maintained.
[0062] As a suitable component (D), a commercially available product can be used, and for example, it can be appropriately selected from the "Novatec" series manufactured by Japan Polyethylene Corporation.
[0063] The component (D) may be a single type of high-pressure low-density polyethylene, or a mixture of two or more types having different physical properties.
[0064] In this embodiment, the content of component (D) relative to the total content of components (A) to (D) is preferably 3 to 30 mass%, more preferably 5 to 25 mass%, and even more preferably 7 to 20 mass%, from the viewpoint of moldability.
[0065] <Component (E): Propylene homopolymer> The polymer composition according to this embodiment may further contain the following component (E). Component (E): Propylene homopolymer
[0066] The density of the component (E) measured by the underwater displacement method in accordance with JIS K 7112:1999 is not particularly limited, but from the viewpoint of mechanical strength, it is preferably 0.890 to 0.910 g / cm 3 and preferably 0.895 to 0.905 g / cm 3 It is more preferable that: The density of component (E) measured by the underwater displacement method in accordance with JIS K 7112:1999 is 0.890g / cm 3By setting the density to 0.910 g / cm or more, the mechanical properties are less likely to deteriorate, and it is preferable that the density is 0.910 g / cm or more. 3 It is preferable that the thickness is not more than 100 mm because the flexibility is less likely to decrease.
[0067] In addition, the MFR (230°C, load 21.2 N, orifice diameter 2 mm) of component (E) measured in accordance with JIS K 7210:2014 is not particularly limited, but from the viewpoints of moldability and compatibility, it is usually 0.01 to 50 g / 10 min, preferably 0.1 to 45 g / 10 min, and more preferably 0.3 to 40 g / 10 min.
[0068] The flexural modulus of the component (E) is not particularly limited, but from the viewpoint of mechanical strength, it is preferably from 1000 to 2000 MPa, and more preferably from 1050 to 1800 MPa.
[0069] As a suitable component (E), a commercially available product can be used, and for example, it can be appropriately selected from MA3 manufactured by Japan Polypropylene Corporation and VX200N manufactured by SunAllomer Corporation.
[0070] <Other ingredients> In the polymer composition according to the present embodiment, additives, polymers, etc. (hereinafter, sometimes referred to as "other components") other than the above-mentioned components can be blended within a range that does not significantly impair the effects of the present invention. The other components may be used alone or in any combination and ratio of two or more.
[0071] Additives that can be used in the polymer composition according to the present embodiment are not particularly limited, but specific examples thereof include heat stabilizers, weather stabilizers (antioxidants, light stabilizers, ultraviolet absorbers, etc.), flame retardants, antiblocking agents, slip agents, antistatic agents, fillers (inorganic and / or organic fillers, etc.), processing aids, plasticizers, crystal nucleating agents, impact improvers, compatibilizers, neutralizers for catalyst residues, carbon black, colorants (pigments, dyes, etc.), etc. When these additives are used, their content is not particularly limited, but it is desirable that they are contained in an amount of usually 0.01% by mass or more, preferably 0.2% by mass or more, and usually 5% by mass or less, preferably 2% by mass or less, based on the total amount of the polymer composition.
[0072] The resin used as the other component is not particularly limited, but examples thereof include polyphenylene ether resins; polycarbonate resins; polyamide resins such as nylon 66 and nylon 11; polyester resins such as polyethylene terephthalate and polybutylene terephthalate, styrene resins such as polystyrene, and acrylic / methacrylic resins such as polymethyl methacrylate resins.
[0073] <Method of producing polymer composition> The polymer composition according to this embodiment can be obtained by mixing the above-mentioned components in a predetermined ratio. The mixing method is not particularly limited as long as the raw material components are uniformly dispersed. That is, the raw material components described above are mixed simultaneously or in any order to obtain a composition in which each component is uniformly dispersed.
[0074] For more uniform mixing and dispersion, it is preferable to melt-mix a predetermined amount of the above-mentioned raw material components. For example, the raw material components of the polymer composition according to the present embodiment may be mixed in any order and then heated, or all the raw material components may be mixed while being melted in sequence, or a mixture of the raw material components may be pelletized or melt-mixed during molding to produce the target molded product.
[0075] The polymer composition according to the present embodiment can be prepared by a method of mixing predetermined amounts of the above-mentioned raw material components using various known methods, for example, a tumbler blender, a V blender, a ribbon blender, a Henschel mixer, etc., and then melt-kneading and granulating or pulverizing the mixture using a single-screw extruder, a twin-screw extruder, a Banbury mixer, a kneader, etc. The temperature during melt-kneading may be any temperature at which at least one of the raw material components is in a molten state, but a temperature at which all the components used are melted is usually selected, and is generally in the range of 150 to 300°C.
[0076] [Laminate and method for manufacturing laminate] <Molded articles and monolayer films made from polymer compositions> The molded article obtained from the polymer composition according to the present embodiment is not limited, and may be various extrusion molded articles or injection molded articles. Specifically, a monolayer film containing the polymer composition according to the present embodiment may be mentioned.
[0077] The monolayer film according to the present embodiment may be a monolayer film (I) made of the polymer composition according to the present embodiment, or may be a monolayer film (II) containing the polymer composition according to the present embodiment and other components. Here, the other components include an olefin-based polymer different from the constituent components of the polymer composition according to the present embodiment as an option. For example, the monolayer film (II) may contain the polymer composition according to the present embodiment and an olefin-based polymer different from the constituent components of the polymer composition according to the present embodiment.
[0078] The monolayer film (II) may be obtained by molding a mixture obtained by dry-mixing the polymer composition according to this embodiment with other components. Such a monolayer film (II) can be obtained, for example, by a method for producing a monolayer film, which includes a step of dry-mixing the polymer composition according to the present embodiment with other components to obtain a dry mixture, and a step of molding the mixture to obtain a monolayer film.
[0079] There is no particular limitation on the thickness of such a monolayer film (I) or monolayer film (II), but it is usually about 5 to 500 μm.
[0080] [Laminate and method for manufacturing laminate] The laminate according to the present embodiment can be a laminate including an adhesive layer containing the polymer composition according to the present embodiment and a substrate layer. Examples of the laminate include a laminate having two or more layers, specifically a laminate sheet, a laminate film, a laminate tube, etc. Here, the terms "sheet" and "film" both mean planar molded bodies and are synonymous.
[0081] The material constituting the base layer of the laminate according to this embodiment is not particularly limited, but is preferably a resin layer, a metal layer made of a metal material, or a metal layer made of a composite material of metal and resin, and more preferably a metal layer made of a metal material or a metal layer made of a composite material of metal and resin.
[0082] The adhesive layer made of the polymer composition according to this embodiment and the substrate layer are preferably adjacent to each other.
[0083] As a method for producing the laminate according to the present embodiment, various known methods can be adopted, but extrusion lamination is particularly suitable. Extrusion lamination is a molding method in which a molten polymer composition is extruded into a film shape, cast onto a substrate, and sandwiched between rolls for pressure bonding to adhere the film.
[0084] As the monolayer film of the polymer composition for forming the adhesive layer, a monolayer film (I) made of the polymer composition according to the present embodiment described above or a monolayer film (II) obtained from a mixture obtained by dry-mixing the polymer composition according to the present embodiment with other components can be used.
[0085] When the substrate layer is a resin layer, the resin layer is preferably obtained by a resin film or sheet. The resin constituting the resin film or sheet is not particularly limited, but specifically, thermoplastic resins such as olefin-based polymers and olefin-based elastomers including ethylene-vinyl alcohol copolymers, ethylene-vinyl acetate copolymers, polyvinyl chloride, polyvinylidene chloride, polyethylene, polypropylene, poly4-methyl-1-pentene, polycarbonate resins, polyamide resins such as polyamide 6, polyamide 66, polyamide 6-66, and polyamide 12, polyester resins and polyester-based elastomers such as polyethylene terephthalate and polybutylene terephthalate, styrene-based resins and styrene-based elastomers, and acrylic resins are preferably used. Among them, when used as a material for food or medical use, it is preferable to have at least a polyester resin layer, an ethylene-vinyl alcohol copolymer layer, or a polyamide resin layer, and more preferably to have at least a polyester resin layer. These resin layers may be formed by laminating two or more kinds of resin layers.
[0086] When the substrate layer is a metal layer made of a metal material or a metal layer made of a composite material of metal and resin, the metal layer is preferably obtained as a film or sheet made of a metal material or a composite material of metal and resin. As the metal, for example, aluminum, SUS material, copper, and titanium are preferably used. As the resin, for example, propylene-based polymers, ethylene-based polymers, ester-based polymers, and nylon-based polymers are preferably used.
[0087] The form of the substrate is not limited to a film or a sheet, and may be a woven fabric or a nonwoven fabric. The substrate may be a single-layer structure or a multi-layer structure. The method for producing a multi-layer substrate is not particularly limited, and examples thereof include a co-extrusion film method, a dry lamination method, a wet lamination method, a hot melt lamination method, an extrusion lamination method, and a thermal lamination method.
[0088] There is no particular limitation on the thickness of such a base layer, but it is usually about 5 to 150 μm.
[0089] The thickness of each layer of the laminate according to this embodiment is not limited and can be set arbitrarily depending on the layer structure, application, shape of the final product, required physical properties, etc. The total thickness of the laminate is usually 5 to 400 μm, preferably 10 to 300 μm, and more preferably 20 to 200 μm. The thickness of the adhesive layer made of the polymer composition according to this embodiment constituting the laminate is usually 0.1 to 300 μm, preferably 1 to 250 μm, and more preferably 5 to 200 μm.
[0090] The laminate thus produced can be further subjected to various film processing treatments such as metal deposition processing, corona discharge processing, printing processing, and the like.
[0091] The polymer composition according to this embodiment exhibits excellent adhesive strength properties to metal layers and resin films, and therefore the laminate according to this embodiment using this polymer composition is suitable for packaging applications such as various foods and beverages, pharmaceuticals and medical products, cosmetics, clothing, stationery, and other industrial materials such as batteries. EXAMPLES
[0092] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. Note that the values of various manufacturing conditions and evaluation results in the following examples are meant as preferred upper or lower limits in this embodiment, and the preferred range may be a range defined by a combination of the above-mentioned upper or lower limit values and the values of the following examples or values of the examples.
[0093] [Measurement and evaluation method] The raw materials used in the following examples and comparative examples, and the measurement and evaluation methods for the obtained polymer compositions and laminates are as follows.
[0094] (1) Melt flow rate (MFR) The MFR of the raw materials was measured at a temperature of 230°C or 180°C and a load of 21.2 N in accordance with JIS K 7210:2014. For materials with extremely high fluidity, the orifice diameter was reduced to measure the MFR, and the value converted to a specified orifice diameter was calculated.
[0095] (2) Graft ratio The pellets of the modified propylene-based polymer were press-molded at 230° C. to obtain a film-like sample having a thickness of 100 μm. The infrared absorption spectrum of the obtained sample was measured using an FT-IR device (JASCO FT / IR610, manufactured by JASCO Corporation), and the graft ratio was calculated from the measurement results.
[0096] (3) Heat of fusion / melting point Using a differential scanning calorimeter (DSC), the temperature was first raised to 200°C to erase the thermal history, then the temperature was lowered to 40°C at a rate of 10°C / min, and then raised again at a rate of 10°C / min. The endothermic peak top temperature was measured and taken as the melting point. The unit is °C. The heat of fusion was calculated from the integral value of the endothermic peak from 80°C to 170°C. The unit is mJ / mg.
[0097] (4) Density The measurement was performed by the underwater displacement method in accordance with JIS K 7112:1999.
[0098] (5) Viscoelasticity The measurement was carried out using a rheometer under the following conditions. Temperature: -100~300℃ Frequency: 1Hz Heating rate: 3℃ / min Distortion: 0.03~0.1% Directionality: No direction
[0099] [raw materials] In the following Examples and Comparative Examples, the raw materials used in the production of the polymer compositions are as follows.
[0100] <Component (A)> A-1 As a modified propylene polymer, a commercially available propylene homopolymer (density: 0.900 g / cm 3 A modified propylene polymer (graft ratio: 2.2 mass%, MFR (value measured at 180°C, load 21.2 N, orifice diameter 1 mm converted to condition of orifice diameter 2 mm): 7200 g / 10 min) obtained by graft-modifying a propylene-based polymer having a MFR (230°C, load 21.2 N, orifice diameter 2 mm): 10 g / 10 min, flexural modulus: 1500 MPa) with maleic anhydride was used.
[0101] <Ingredient (B)> B-1 Storage modulus 100℃: 190MPa, 120℃: 73MPa, MFR (230℃, load 21.2N, orifice diameter 2mm): 7.0g / 10min, density: 0.900g / cm 3 A propylene-ethylene copolymer with a propylene content of 96.2% by mass and an ethylene content of 3.8% by mass was used. B-2 Storage modulus 100℃: 34MPa, 120℃: 8MPa, MFR (230℃, load 21.2N, orifice diameter 2mm): 20g / 10min, density: 0.890g / cm 3 A propylene-ethylene copolymer with a propylene content of 94.0% by mass and an ethylene content of 6.0% by mass was used. B-3 Storage modulus 100℃: 263MPa, 120℃: 139MPa, MFR (230℃, load 21.2N, orifice diameter 2mm): 30g / 10min, density: 0.900g / cm 3 A propylene-ethylene copolymer with a propylene content of 99.3% by mass and an ethylene content of 0.7% by mass was used. B-4 The propylene-ethylene copolymer used was PZA20A manufactured by Sunallomer Co., Ltd. (storage modulus 100°C: 227 MPa, 120°C: 136 MPa, MFR (230°C, load 21.2 N, orifice diameter 2 mm): 44 g / 10 min, propylene content: 98.2 mass%, ethylene content: 1.8 mass%). B´-1 As a propylene-ethylene copolymer, ExxonMobil's Vistamax 3000 (storage modulus 100°C: 0.1 MPa or less, 120°C: 0.1 MPa or less, MFR (230°C, load 21.2 N, orifice diameter 2 mm) 8.0 g / 10 min, density 0.871 g / cm 3 A copolymer having a propylene content of 89% by mass and an ethylene content of 11% by mass was used.
[0102] <Component C> C-1 As an ethylene-propylene copolymer, Toughmer P0180 manufactured by Mitsui Chemicals Inc. (MFR (230°C, load 21.2N, orifice diameter 2mm): 5.4g / 10min, density: 0.870g / cm 3 , melting point: 40° C., ethylene content: 74.5% by mass, propylene content: 25.5% by mass was used. C-2 As an ethylene-1-butene copolymer, Toughmer A4085S (MFR (190°C, load 21.2N, orifice diameter 2mm) 3.6g / 10min, density 0.885g / cm) manufactured by Mitsui Chemicals, Inc. was used. 3 A copolymer having an ethylene content of 85.0% by mass and a 1-butene content of 15.0% by mass was used.
[0103] <Ingredient (D)> D-1 As a high-pressure low-density polyethylene, Novatec LDLC-522 (MFR (190°C, load 21.2N, orifice diameter 2mm): 4g / 10min, density: 0.913g / cm) manufactured by Japan Polyethylene Co., Ltd. 3 ) was used. D-2 As a high-pressure low-density polyethylene, Novatec LDLC-701 (MFR (190°C, load 21.2N, orifice diameter 2mm): 14g / 10min, density: 0.918g / cm) manufactured by Japan Polyethylene Co., Ltd. 3 ) was used.
[0104] <Ingredient (E)> E-1 As a propylene homopolymer, MA3Q (density 0.900 g / cm) manufactured by Japan Polypropylene Corporation was used.3 , MFR (230°C, load 21.2 N, orifice diameter 2 mm): 10 g / 10 min, flexural modulus: 1500 MPa) was used.
[0105] [Example 1] <Production of polymer composition> 9 parts by mass of A-1, 32 parts by mass of B-1, 10 parts by mass of B-2, 16 parts by mass of B-4, 13 parts by mass of C-1, 15 parts by mass of D-2, and 5 parts by mass of E-1 described in the above [Raw Materials] were dry blended and mixed, and melt kneaded using a twin-screw extruder (manufactured by The Japan Steel Works, Ltd., TEX25, D=25mmφ, L / D=43) at a set temperature of 180-210°C, a screw rotation speed of 250-350 rpm, and an extrusion rate of 15-40 kg / h, and then strand cut to obtain a pellet-shaped polymer composition according to Example 1.
[0106] <Forming of extrusion laminate film> Using an extrusion lamination device (manufactured by Sumitomo Heavy Industries Modern Co., Ltd.) having a T-die equipped with two extruders A and B with a diameter of 40 mm, the obtained polymer composition was fed to the extruder A, and a polypropylene-based polymer (manufactured by Japan Polypropylene Corporation, Novatec PPFL02G) was fed to the extruder B. The distribution block was set so that the layer formed by the extruder A was disposed on the substrate film side, and the temperatures of the resins extruded in the two layers were both set to 280 to 290 ° C., and the air gap was set to 120 mm, the cooling roll surface temperature to 20 ° C., the die width to 360 mm, the die lip opening to 0.7 mm, and the take-up processing speed to 50 m / min. Then, the extrusion amount was adjusted so that the coating thickness of the polymer composition layer was 10 μm and the coating thickness of the polypropylene-based polymer layer was 10 μm, and the extrusion laminate film according to Example 1 was formed. Here, the base film used was Alpet (thickness: 62 μm, composite film of aluminum and PET) manufactured by Panac Corporation. The polymer composition layer was disposed so as to be in contact with the aluminum surface of the base film.
[0107] The polymer composition and extrusion laminate film according to Example 1 were evaluated according to the following procedures. The results are shown in Table 1.
[0108] <Evaluation: Adhesive strength> The extrusion laminate film obtained above was cut into a 10 mm wide strip to prepare a test piece, and a T-peel type peel test was carried out at a speed of 300 mm / min in a thermostatic chamber adjusted to 100°C and 120°C to measure the peel strength, which was taken as the adhesive strength of the extrusion laminate film. The higher the adhesive strength number, the better the adhesiveness.
[0109] <Evaluation: Formability> The drawdown characteristics were evaluated as an evaluation of formability when the above extrusion laminate film was molded. Using an extrusion lamination device (manufactured by Sumitomo Heavy Industries Modern Co., Ltd.) having a T-die equipped with two extruders A and B with a diameter of 40 mm, the obtained polymer composition was fed to the extruder A, and a distribution block was set so that the layer formed by the extruder A was disposed on the kraft paper substrate, and extrusion lamination molding was performed without using the extruder B. The temperature of the resin was set to 280 to 290 ° C, and the extrusion amount was adjusted so that the coating thickness of the polymer composition layer was 10 μm at an air gap of 120 mm, a cooling roll surface temperature of 20 ° C, a die width of 360 mm, a die lip opening of 0.7 mm, and a molding speed of 50 m / min. The extrusion amount was adjusted to extrude and form a film. At this time, the molding speed was increased with the extrusion amount of the adhesive resin layer fixed, and the limit speed at which the film breakage occurred was confirmed. The larger the limit speed number, the better the drawdown characteristics, and if it is 50 m / min or more, it can be evaluated as practical moldability.
[0110] [Table 1]
[0111] [Example 2, Comparative Example 1] The pellet-shaped polymer compositions and extrusion laminate films according to Example 2 and Comparative Example 1 were obtained in the same manner as in Example 1, except that the blending compositions shown in Table 1 were used. The obtained polymer composition and extrusion laminate film were evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0112] The results shown in Table 1 show that the polymer compositions and extrusion laminate films of Examples 1 and 2 have excellent moldability and high adhesive strength in a high-temperature environment. In contrast, it was found that the polymer composition and extrusion laminate film of Comparative Example 1 had low adhesive strength in a high-temperature environment. [Industrial Applicability]
[0113] The polymer composition according to this embodiment exhibits excellent adhesive strength properties to metal layers and resin films, and therefore the laminate according to this embodiment using this polymer composition is suitable for packaging applications such as various foods and beverages, pharmaceuticals and medical products, cosmetics, clothing, stationery, and other industrial materials such as batteries.
Claims
1. A polymer composition comprising the following components (A) to (D): Component (A): A modified propylene-based polymer obtained by modifying a propylene-based polymer with an unsaturated carboxylic acid and / or a derivative thereof. Component (B): at least one propylene-based copolymer selected from the group consisting of propylene-ethylene copolymers, propylene-α-olefin copolymers, and propylene-ethylene-α-olefin copolymers, the propylene-based copolymer having a storage modulus at 120° C. of 6 to 300 MPa. Component (C): Density measured by underwater displacement method in accordance with JIS K 7112: 1999 is 0.855 to 0.910 g / cm 3 Ethylene / α-olefin copolymer Component (D): High-pressure low-density polyethylene
2. The polymer composition according to claim 1, wherein the content of the component (B) relative to the total content of the components (A) to (D) is 45 to 75 mass%.
3. 2. The polymer composition according to claim 1, wherein the component (B) is a propylene-ethylene copolymer.
4. The polymer composition according to claim 1, wherein the content of propylene units in the component (B) is 90 to 99.5 mass%.
5. A monolayer film comprising the polymer composition according to any one of claims 1 to 4.
6. A laminate comprising an adhesive layer containing the polymer composition according to any one of claims 1 to 4 and a substrate layer.
7. The laminate according to claim 6 , wherein the substrate layer is a metal layer made of a metal material or a metal layer made of a composite material of a metal and a resin.
Citation Information
Patent Citations
Resin composition and laminated body
JP2012188662A